2000
DOI: 10.1590/s0102-311x2000000100009
|View full text |Cite
|
Sign up to set email alerts
|

Validade do exame clínico do recém-nascido para a estimação da idade gestacional: uma comparação do escore New Ballard com a data da última menstruação e ultra-sonografia

Abstract: The objective of this article is to evaluate the accuracy of the New Ballard (NB) score in detecting prematurity. Date of last menstrual period (LMP) and ultrasonography (USG) are used as reference procedures. First, an assessment of inter-observer reliability of the NB score measurements and the USG reports was carried out. Regarding the NB scores, the kappa coefficient and the Intraclass Correlation Coefficient were, respectively, (IC 95%: 0,99) e 0,88 (IC 95%: 0,93), respectivamente. Na avaliação das ultra-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
8

Year Published

2005
2005
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
5
0
8
Order By: Relevance
“…Several suggest, as did the present one, that the Ballard score overestimated the gestational age in preterm infants leading to an underestimation of the percentages of preterm infants [32,33]. A study from Brazil reported poor sensitivity (70%) in detecting preterm infants when compared with ultrasonography [34]. In one study from Malawi, the external features of the Ballard were reliably obtained by nurses and led to an improvement in gestational age assessment when compared with dating by the last menstrual period or the fundal height [35].…”
Section: Discussionmentioning
confidence: 59%
“…Several suggest, as did the present one, that the Ballard score overestimated the gestational age in preterm infants leading to an underestimation of the percentages of preterm infants [32,33]. A study from Brazil reported poor sensitivity (70%) in detecting preterm infants when compared with ultrasonography [34]. In one study from Malawi, the external features of the Ballard were reliably obtained by nurses and led to an improvement in gestational age assessment when compared with dating by the last menstrual period or the fundal height [35].…”
Section: Discussionmentioning
confidence: 59%
“…Ultrasound, as a tool to assess gestational age, is a limiting factor, particularly in developing countries, like India where only 51% of women undergo the recommended number of at least 3 antenatal visits; 59% of deliveries take place at home; and only 24% of pregnant women undergo ultrasonic evaluation during pregnancy (8). Assessment of gestational age of newborns using New Ballard Score (NBS) may not be reliable as its accuracy depends on the skill of examiner (9) and the condition of the neonate. It cannot be used in asphyxiated neonates.…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, despite the disagreement between the gestational age recorded in the hospital database and that of SINASC, all newborns were classified as premature (birth before 37 weeks of pregnancy), an expected fact when working with very low weight newborns. However, for epidemiological studies with SINASC data and that include newborns of all weight ranges, the inaccuracy of the gestational age recorded on the DN may be a potential source of difficulties in the identification of prematurity and of prematurity associated risk factors 7,29 .…”
Section: Discussionmentioning
confidence: 99%